2008
DOI: 10.1590/s0103-50532008000100009
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid and iron evaluation in Brazilian enriched corn and wheat flours

Abstract: O ácido fólico tem sido identificado como uma das mais importantes vitaminas para a função normal do metabolismo humano. A deficiência de ferro é um sério problema de saúde que afeta uma grande proporção da população do mundo. No Brasil, foi publicada uma regulamentação indicando que farinhas de milho e trigo devem ser fortificadas com ácido fólico e ferro. O objetivo deste trabalho foi avaliar os níveis de ácido fólico e ferro em algumas farinhas enriquecidas. A quantificação de ambos nutrientes indicou que a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
11

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 15 publications
1
13
1
11
Order By: Relevance
“…These values are within the range of 80 to 110% set by the AOAC [28]. Studies were found in the literature with similar percentages for the recovery of thiamin, of between 73 to 106% [21,23,24] and 81 to 103% for folic acid [25,27,29]. …”
Section: Recoverysupporting
confidence: 68%
See 2 more Smart Citations
“…These values are within the range of 80 to 110% set by the AOAC [28]. Studies were found in the literature with similar percentages for the recovery of thiamin, of between 73 to 106% [21,23,24] and 81 to 103% for folic acid [25,27,29]. …”
Section: Recoverysupporting
confidence: 68%
“…The value found for thiamin was lower than the limits of detection found by Hucker et al [24], Presoto and AlmeidaMuradian [25], and San José Rodriguez [22], being 0.02 μg, 0.03 μg, and 0.06 μg, respectively. In relation to folic acid, values of 0.003 μg, 0.0013 μg, and 0.06 μg were found by Boen et al [26], Lebiedziñska et al [27], and Alaburda et al [28], respectively.…”
Section: Limits Of Detection and Quantificationcontrasting
confidence: 60%
See 1 more Smart Citation
“…A study on a total of 70 samples of flour from supermarkets in the cities of Campinas and São Paulo State, one of the states with significantly reduced risk of anencephaly ( Table 2), showed that the concentration of folic acid ranged between 96 and 558 mg per 100 g (in corn) and 73-233 mg per 100 g (in wheat). These results showed a great variation in FA concentration, and that the Brazilian population would seem to be most likely exposed to inadequate concentrations of FA (Rezende Boen et al 2008) (Tables 2 and 3). In this study, on the one hand, the concentrations were very close or lower than the issued value (wheat flours).…”
Section: Discussionmentioning
confidence: 91%
“…No Brasil, em análise de seis marcas de farinha de milho e oito de farinha de trigo, Boen et al (2008) verificaram que a concentração de ácido fólico variava de 96 a 558g/100g nas farinhas de milho, sendo que cinco apresentavam média acima dos 150g/100g de farinha estabelecido na legislação; nas farinhas de trigo, a concentração média variava de 73 a 233g/100g e duas apresentavam quantidade superior ao estabelecido. Assim, é fundamental controlar rigorosamente a quantidade de ácido fólico presente nas farinhas e monitorar os programas de fortificação para documentar os reais benefícios dessa estratégia para a saúde pública (Crider et al, 2011).…”
Section: Finalidade E Questões De Pesquisaunclassified